The Crime of Feminicide: Violence against Women for Gender Reasons - Rivas La Madrid, Sofia (2024)
The work analyzes the international instruments that recognize the human rights of women and how the States parties have adopted special temporary measures aimed at achieving substantive equality between women and men. In the case of the Peruvian State, it provides an account of the legal reception of its responsibilities assumed as a State Party regarding the recognition and protection of women's human rights, and how Peruvian jurisprudence interprets and applies them. The legislative background of the law that incorporated the criminal offense of feminicide will be analyzed, as well as the reasons that justify this regulatory change. Likewise, the current problem regarding the objective typicality in these cases is developed, given the discrepancies in criteria regarding the analysis of the active and passive subject of the crime of feminicide. Finally, the conclusions of the research are formulated.